Absence of adverse hepatic or renal effects with the etonogestrel-releasing contraceptive implant inserted immediately postpartum - Milena B Brito; Rui A Ferriani; Silvana M Quintana; et al (Dove Medical Press, 2010)
Milena B Brito1,2, Rui A Ferriani1,2, Silvana M Quintana1, Marcos F Silva de Sá1,2, Carolina S Vieira1,21Department of Gynecology and Obstetrics, University of Sao Paulo, Ribeirao Preto School of Medicine, Ribeirão Preto, Brazil; 2National Institute of Hormones and Women’s Health, Ribeirão Preto, BrazilObjective: To evaluate the safety, in terms of renal and hepatic function, of the etonogestrel (ENG)-releasing contraceptive implant inserted immediately postpartum.Methods: A total of 40 healthy women were randomized; 20 received the ENG-releasing implant inserted 24 to 48 hours after delivery (ENG group), and 20 received depot medroxyprogesterone acetate in the sixth week postpartum (control group). Alkaline phosphatase, gamma-glutaryl transferase, alanine aminotransferase, aspartate aminotransferase, total bilirubin and its fractions, albumin, urea, and creatinine were analyzed.Results: There was no statistically significant difference between the groups in serum hepatic markers or urea levels during the study. Creatinine levels increased in both groups during the first six weeks, more significantly in the ENG group than in the control group (ENG +40% versus control +20%, P = 0.04). This increase was followed by a greater decrease in the ENG group than in the control group 6–12 weeks postpartum (ENG -14.3% versus control -3.8%, P = 0.02). However, these changes were still within the normal ranges for the assays performed.Conclusion: The ENG-releasing contraceptive implant inserted immediately postpartum was not associated with clinically significant changes in serum markers of liver or kidney function.Keywords: etonogestrel, renal, hepatic, postpartum period, contraception, implant